Principles of financial economics - Leroy, Stephen F (Cambridge University Press, 2001)
'This is an excellent introduction to the exciting field of financial economics, rigorous yet filled with economic intuition, and with a refreshing emphasis on equilibrium that is reminiscent of Debreu's elegant and pithy monograph.' Andrew Lo, Massachusetts Institute of Technology